Sulphonated biomass-based catalyst for solketal synthesis by acetalization of glycerol – A byproduct of biodiesel production - Saikia, Kankana; Rajkumari, Kalyani; Moyon, N. Shaemningwar; Basumatary, Sanjay; Halder, Gopinath; Rashid, Umer; Rokhum, Samuel Lalthazuala (Elsevier, 2022)
Research on biomass-based catalyst is beneficial for the sustainability of biodiesel industry owing to its wide availability of feedstock, non-toxicity and biodegradability. Cellulose based heterogeneous solid carbon catalyst was prepared from cellulose by treating cellulose with concentrated sulphuric acid in innocuous hydrothermal conditions. It shows promising potential as a suitable catalyst for the synthesis of solketal (a biofuel additive) by acetalization of glycerol, the waste product of biodiesel production. 97.1 ± 0.4% of solketal was produced under the optimum conditions of 1:5 M ratio of glycerol and acetone, catalyst loading of 7 wt% at 70 °C in 10 min. 90% of catalytic activity was retained even after five catalytic cycles making the catalyst highly efficient. With further investments; this method may be used for the preparation of biofuel additive in an industrial level.